3(f-2)=7(f+2)

Simple and best practice solution for 3(f-2)=7(f+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(f-2)=7(f+2) equation:


Simplifying
3(f + -2) = 7(f + 2)

Reorder the terms:
3(-2 + f) = 7(f + 2)
(-2 * 3 + f * 3) = 7(f + 2)
(-6 + 3f) = 7(f + 2)

Reorder the terms:
-6 + 3f = 7(2 + f)
-6 + 3f = (2 * 7 + f * 7)
-6 + 3f = (14 + 7f)

Solving
-6 + 3f = 14 + 7f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-7f' to each side of the equation.
-6 + 3f + -7f = 14 + 7f + -7f

Combine like terms: 3f + -7f = -4f
-6 + -4f = 14 + 7f + -7f

Combine like terms: 7f + -7f = 0
-6 + -4f = 14 + 0
-6 + -4f = 14

Add '6' to each side of the equation.
-6 + 6 + -4f = 14 + 6

Combine like terms: -6 + 6 = 0
0 + -4f = 14 + 6
-4f = 14 + 6

Combine like terms: 14 + 6 = 20
-4f = 20

Divide each side by '-4'.
f = -5

Simplifying
f = -5

See similar equations:

| C+5-2x=3+x | | -4y+b= | | 4(x+5)=-4x-20 | | 12n+22=5 | | 18d+18+20=2(15d-17) | | 5(x+1)-6x=-11x | | f(p)=p^2-6p+1 | | y=3500x+31500 | | y-14=y | | 2.8v-3.54-17.4v=-9.19-15.1v | | 12n+22=44 | | (x-3/2)^2-5/4=0 | | 10-5s=-10-3s | | (2x-7)/5=4⋅(x-2) | | 5(2k+3)-8=6p+29 | | 12n+22=128 | | 0.0003x=1 | | 16.2s-16.76=16.7s-15.26 | | 10d=9+9d | | 12n+22=125 | | m-2/3=-1/2 | | 15-3h=2h+2 | | -10.8n+5.16=-11.2n | | -6c-6=-5c | | (x-3/2)2-5/4=0 | | 0.45+15.1k=18.3+16.8k | | x(3x+3)=0 | | 109=-7+18 | | -x-4x=20 | | -16-(-2m)=8m+12 | | 19.6b-7.45=14.1b+17.9+6.8b | | -7m=-8m+9 |

Equations solver categories